2019
DOI: 10.1080/21691401.2019.1593995
|View full text |Cite
|
Sign up to set email alerts
|

Association between NOS3 polymorphisms and osteonecrosis of the femoral head

Abstract: Purpose: This study aimed to detect the association between nitric oxide synthase 3 (NOS3) gene polymorphisms (rs1799983 and rs3918181) and the susceptibility to osteonecrosis of the femoral head (ONFH). Methods: Total 88 ONFH patients (55 non-traumatic ONFH and 33 traumatic ONFH) and 90 healthy controls were recruited in this case-control study. Polymerase chain reaction-restriction fragment length polymorphism(PCR-RFLP) was adopted for genotyping NOS3 rs1799983 and rs3918181 polymorphisms. v 2 test was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…With the progress of molecular technology, the amount of research studies have observed the genetic factors, such as glutamate receptor gene [ 9 ], single nucleotide polymorphisms and transient receptor potential vanilloid 4 gene [ 10 ], and nitric oxide synthase 3 gene [ 11 ], have been accepted to influence the etiology of ONFH. In recent years, an increasing number of studies have manifested that microRNAs have been directly in the regulation of bone development and regeneration in orthopedic diseases, such as osteosarcoma [ 12 ], knee osteoarthritis [ 13 ], and lumbar disc herniation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the progress of molecular technology, the amount of research studies have observed the genetic factors, such as glutamate receptor gene [ 9 ], single nucleotide polymorphisms and transient receptor potential vanilloid 4 gene [ 10 ], and nitric oxide synthase 3 gene [ 11 ], have been accepted to influence the etiology of ONFH. In recent years, an increasing number of studies have manifested that microRNAs have been directly in the regulation of bone development and regeneration in orthopedic diseases, such as osteosarcoma [ 12 ], knee osteoarthritis [ 13 ], and lumbar disc herniation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, for some cases, even small doses of corticosteroid could cause osteonecrosis and genetic predisposition may contribute the result. Genetic polymorphisms in many genes including SERPINE1, VEGF, VDR, CYP3A4, ACP1, and NOS3 are reported to be associated with ONFH [23]. These genes also play an important role in MM susceptibility and drug effects.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the role of genetic polymorphisms in the development of ONFH has been widely reported. For example, Zhao et al found that NOS3 variants were associated with the occurrence of ONFH [8]. A meta-analysis by Song et al showed that eNOS polymorphism was correlated with idiopathic and secondary ONFH in Caucasians and Asians [9].…”
Section: Introductionmentioning
confidence: 99%